Breast Cancer to Brain Metastases unknown Reboot until Trauma: A Case Report and Literature Review - Encarnación Santos, Daniel Antonio; Pachev, Murat; Shestov, Eugeny; Chmutin, Gennady; Chmutin, Egor; Shodikhon, Jamdshedi (Asian Pacific Journal of Cancer Care, 2025)
Background: The Aim is to analyze the therapeutic, surgical, and nonsurgical benefits of removing brain tissue that interferes with the patient’s daily routine, while adding conservative hormonal management to the postoperative period. Case Presentation: We present the case of a 57-year-old woman with a history of left breast cancer (T2N0M0, Stage 2A) who developed neurolgical symptoms secondary to an intracerebral tumor in the right occipital lobe. Initial symptoms included unconsciousness and focal neurological deficits. Imaging revealed a cystic lesion with significant perifocal edema and mass effect. A surgical intervention involving osteoplastic craniotomy was performed, and histopathology confirmed metastasis from breast adenocarcinoma. Postoperatively, the patient exhibited clinical and radiological improvement with a reduction in neurological symptoms and mass effect. Conclusion: Multidisciplinary care was critical in managing this patient, resulting in symptomatic improvement and positive postoperative dynamics. This case reinforces the importance of tailored treatment plans involving surgery and adjuvant therapies for patients with brain metastases from breast cancer.